Analisis Catch Per Unit Effort (CPUE) dan Maximum Sustainable Yield (MSY) Ikan Layang (Decapterus sp) Yang Didaratkan di Pelabuhan Perikanan Samudera (PPS) Kendari - windhi mulia; Andi Irwan Nur; Utama Kurnia Pangerang (Universitas Mataram, 2024)
The Banda Sea is one of the most fertile and potential waters in the field of fisheries and the largest fishing area in Indonesia. This study aims to analyze the CPUE and MSY of indian scad from 2016-2022 (last 7 years). The value of Catch per Unit Effort (CPUE) fluctuated from 2016-2022. The highest purse seine equivalent CPUE value in 2018 was 4,562 kg/trip and the lowest in 2021 was 2,573 kg/trip. Based on the Schaefer model, the optimum fishing effort value is 3,382 trips per year and the maximum sustainable catch value is 7,936,016 kg per year. From this value, it indicates that the indian scad landed at PPS Kendari is underfished because it has not reached its sustainable potential